Scrutinizing Metadiscourse Markers in the Gossip Columns of Lambe Turah and Insert Live: A Corpus Linguistic Study - Yusnidar, Lira; Prihantoro, Prihantoro; Sahila Rizqy, Muhammad Hifni; Anggraeni, Mariah (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
The use of meta-discourse in academic spoken or written texts has been widely investigated. However, the existence of meta-discourse as a meaning-making in informal contexts such as gossip pages remains unaddressed. This present study investigates the frequency of word classes and the use of meta-discourse markers as the meaning-making practices in the gossip columns of Insert Live and Lambe Turah. The selection of these two online media platforms is grounded in their pragmatics and national coverage. The data collection of this research utilizes the corpus method. Data were gathered from Insert Live and Lambe Turah gossip columns. In accordance with Hyland's theory (2005), the focus of this study is on comparing the word list frequency and functions of meta-discourse markers in the gossip columns in online media. The finding reveals that Insert Live tends to emphasize object-related elements, while Lambe Turah tends to underscore event-related aspects in gossip reporting. Besides, Insert Live tends to use meta-discourse markers in gossip columns to provide clarifications derived from informants, while Lambe Turah employs meta-discourse markers to steer readers’ opinions toward believing a particular issue by producing accusations using speculative language.